HUKUMAN MATI BAGI KORUPTOR DALAM PERSPEKTIF HUKUM ISLAM - Agus Gede Sutamaya; Yudi Kurniawan; Neneng Nurhasanah (Jurnal Dialektika Hukum, 2022)
As the majority of Indonesian citizens, Muslims cannot avoid that a lot of corruption is carried out by people who are Muslim. In Indonesia's positive law, there are still some crimes that carry the death penalty. In Islam, it implies the imposition of punishment that will be able to provide a deterrent effect for perpetrators of corruption, namely the death penalty. One of the arguments that imply the death penalty for perpetrators of corruption is contained in the Qur'an Surah Al-Maidah verse 33. This paper aims to provide thoughts related to the death penalty status for Corruptors in the perspective of Islamic law, so that at least it becomes material reflection and reminding that corruption is a bad act and is strictly prohibited by Islam, because the bad impact it has on a society and nation is very large.